Experimental test of birdcall detection by autonomous recorder units and by human observers using broadcast. Issue 5 (10th February 2019) - Castro, Isabel; De Rosa, Alberto; Priyadarshani, Nirosha; Bradbury, Leanne; Marsland, Stephen
Abstract: Autonomous recording units are now routinely used to monitor birdsong, starting to supplement and potentially replace human listening methods. However, to date there has been very little systematic comparison of human and machine detection ability. We present an experiment based on broadcast calls of nocturnal New Zealand birds in an area of natural forest. The soundscape was monitored by both novice and experienced humans performing a call count, and autonomous recording units. We match records of when calls were broadcast with detections by both humans and machines, and construct a hierarchical generalized linear model of the binary variable of correct detection or not, with a set of covariates about the call (distance, sound direction, relative altitude, and line of sight) and about the listener (age, experience, and gender). The results show that machines and humans have similar listening ability. Humans are more homogeneous in their recording of sounds, and this was not affected by their individual experience or characteristics. Humans were affected by trial and location, in particular one of the stations located in a small but deep valley. Despite recorders being affected significantly more than people by distance, altitude, and line of sight, their overall detection probability was higher. The specific location of recorders seems to be the most important factor determining what they record, and we suggest that for best results more than one recorder (or at least, microphone) is needed at each station to ensure all bird sounds of interest are captured. Abstract : In this paper, we directly compare the detection capabilities of humans and acoustic recorders in the field using an experimental setup with listening and broadcast stations, to examine the effect of factors that we know have an effect on sound transmission (e.g., distance, sound direction, altitude) on human and machine detection of New Zealand bird sounds. Our findings show that while the recorders and humans are similar in the capacity of detecting sounds, the factors we examined have different effects on them. This differences need to be considered when using recorders and humans for surveys, but especially when comparing surveys.